Exploring the Leadership Model of Tgk. H. Syarifuddin, M.A., at the Jannatul Firdaus Integrated Islamic Boarding School - Suryadi, Agus; Mukti, Abd.; Siahaan, Amiruddin; Nasution, Muhammad Amri (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research examines the leadership model of Mr. H. Syarifuddin, MA, founder of Jannatul Firdaus Islamic Boarding School, and how it integrates with the institution's educational programs. The study uses a naturalistic qualitative approach, employing field research methods including observation, interviews, and documentation to ensure reliable and valid findings. The charismatic aspect of Mr. Syarifuddin's leadership is marked by his discipline, firmness, and effective communication with diverse community groups. His transformational approach focuses on motivating students, enhancing their communication and social skills, fostering entrepreneurship, and promoting community integration. These leadership attributes have significantly influenced the school's ability to adapt and thrive, aligning its educational offerings with contemporary societal needs and facilitating the development of both students and the broader community. The findings highlight the effectiveness of combining charismatic and transformational leadership to drive educational and social progress, demonstrating how a well-rounded leadership model can enhance the relevance and impact of educational institutions.